2012
DOI: 10.1007/s10286-012-0179-1
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity intermittent exercise and cardiovascular and autonomic function

Abstract: High-intensity intermittent exercise induced significant cardiac, vascular, and autonomic improvements after 12 weeks of training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
94
3
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(128 citation statements)
references
References 36 publications
9
94
3
2
Order By: Relevance
“…[1,2,9,10] The improvements in HR, SV, CO and EJT in this study indicate improved cardiac efficiency and are consistent with other studies conducted in young, healthy subjects. [9] There are numerous studies documenting an increased SV after a prolonged exercise intervention in both older [18] and young, healthy subjects [9] but specific detailed studies on black Africans are scant. Vella and Robergs [19] suggest that SV response to exercise is influenced by training status, age and sex, but fail to discuss the influence of ethnicity.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…[1,2,9,10] The improvements in HR, SV, CO and EJT in this study indicate improved cardiac efficiency and are consistent with other studies conducted in young, healthy subjects. [9] There are numerous studies documenting an increased SV after a prolonged exercise intervention in both older [18] and young, healthy subjects [9] but specific detailed studies on black Africans are scant. Vella and Robergs [19] suggest that SV response to exercise is influenced by training status, age and sex, but fail to discuss the influence of ethnicity.…”
Section: Discussionsupporting
confidence: 91%
“…[5,8] The majority of studies examining the effect of exercise on cardiac and vascular function have been conducted on caucasian subjects and have found that major adaptations include a lowered resting heart rate, increased stroke volume, improved limb blood flow and limb vasodilatory capacity, and a decrease in arterial stiffness. [9] Autonomic adaptations include increased vagal tone and baroreflex sensitivity. [9,11] Several studies that have been conducted in older African populations suggest that regular exercise has beneficial cardiovascular effects and may decrease the risk for cardiac complications.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Expired gases were analyzed using a Quark b2 breath-bybreath metabolic system (Cosmed, Rome, Italy) while subjects cycled on an ergometer (model H-300-R, Lode) at 30 watt for 3 min as a warm-up, followed by an instantaneous increase of 1 W every 2 s at a cadence above 70 rpm (Heydari et al 2013). The maximal exercise test lasted until attainment of a V′O 2 plateau or the attainment of at least two of the three additional criteria: (1) a plateau of heart rate despite an increased power, (2) inability to maintain the cycling cadence (i.e., dropped by >10 rpm), or (3) exercise cessation due to substantial fatigue.…”
Section: Maximal Oxygen Consumption Evaluation (V′o 2max )mentioning
confidence: 99%
“…The majority of studies on aerobic exercise have investigated the role of high intensity interval training (HIIT), which has been shown to reduce heart rate and arterial stiffness, increase aerobic fitness, stroke volume, limb vasodilatory capacity, heart rate variability, and baroreflex sensitivity in young healthy men after 12 weeks of training (Heydari et al 2013). Now HIIT is the first top fitness trends and it reflects how this form of exercise has taken the fitness community in recent months (Thompson 2013).…”
Section: Introductionmentioning
confidence: 98%